1993
DOI: 10.1016/0370-2693(93)90897-q
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the gluonic EMC effect in associated J/ψ+γ production

Abstract: We study the associated production of J/ψ + γ in fixed-target experiments with nuclear targets as well as at the relativistic heavy-ion collider (RHIC). We find that this process affords a very clean probe of ρ g , the ratio of gluon density in a heavy nucleus to that of a proton. The combined x range thus available can be used to discriminate between the predictions of different models of the EMC effect for ρ g . a) gavai%theory@tifrvax b) rohini%theory@tifrvax c) sridhar@vxcern.cern.ch

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Recently, Drees and Kim advocated [5] the study of associated production of J/ψ and a photon at large p T as a clean probe of the gluon density in pp and ep collisions. We extended [6] their considerations to pA and AA collisions for the fixed target experiments at FNAL and the collider experiments at RHIC. We found that the rates for these processes at both FNAL and RHIC are substantial and a large range of x is covered by combining them, thus enabling a cleaner and better determination of ρ g .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Drees and Kim advocated [5] the study of associated production of J/ψ and a photon at large p T as a clean probe of the gluon density in pp and ep collisions. We extended [6] their considerations to pA and AA collisions for the fixed target experiments at FNAL and the collider experiments at RHIC. We found that the rates for these processes at both FNAL and RHIC are substantial and a large range of x is covered by combining them, thus enabling a cleaner and better determination of ρ g .…”
Section: Introductionmentioning
confidence: 99%
“…In this letter, we suggest that the production of a photon in association with the quarkonium will help to clearly distinguish between these two models of quarkonium formation. The associated production of J/ψ and photon at large p T has been studied in the context of collider [8], fixed-target [9] and polarised pp scattering experiments [10], in the framework of the colour-singlet model; it has been shown to be a very sensitive probe of gluon distributions. This is so because, in the colour-singlet model, the only subprocess that contributes to J/ψ + γ production, with the J/ψ and γ produced back-to-back at large p T , is the following:…”
mentioning
confidence: 99%
“…There has been much interest recently in associated production of a J/ψ and a photon (γ) in collider [1] and fixed-target experiments [2,3]. In the framework of the coloursinglet model [4,5], the QCD subprocess that contributes to the production of a J/ψ and a photon is:…”
mentioning
confidence: 99%
“…The photoproduction process and the process in Eq. ( 1) are gluon-initiated, and have been suggested as sensitive probes of gluon densities in lepton-nucleon experiments [4], and in hadron-nucleon experiments [1,2], respectively. The J/ψ + γ mode is also the decay mode in which the P -state charmonia are detected [6,7].…”
mentioning
confidence: 99%